Assisted Partner Services for People Who Inject Drugs: Index Characteristics Associated With Untreated HIV in Partners. (1st November 2022) - Tseng, Ashley S.; Sambai, Betsy; Monroe-Wise, Aliza; Mbogo, Loice W.; Ludwig-Barron, Natasha T.; Masyuko, Sarah J.; Chohan, Bhavna H.; Scott, John D.; Sinkele, William; Herbeck, Joshua T.; Farquhar, Carey; Guthrie, Brandon L.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Assisted partner services (APSs) is a feasible, acceptable, and effective strategy that increases uptake of HIV testing; however, it has not been used widely among people who inject drugs (PWID) in Africa to notify sexual and injecting partners of potential exposures to HIV and provide testing services. Setting: Nairobi, Kilifi, and Mombasa counties in Kenya. Methods: PWID living with HIV (indexes) were enrolled and asked to provide contact information for sexual and injecting partners who were traced and offered HIV testing. APS efficiency was assessed by the number of indexes needed to interview (NNTI) to find 1 additional partner who was unaware of their HIV status or not on antiretroviral therapy (ART). We defined index participant characteristics associated with greater efficiency, defined as lower NNTIs. Results: Among 783 indexes, the NNTI to identify one partner unaware of their HIV status was 7.1 and to identify one HIV-positive partner not on ART (regardless of status awareness) was 4.1. APS was provided to 977 partners and was more efficient in identifying partners who were not on ART (n = 201) among indexes who were female (NNTI = 2.9 vs. 5.7, P < 0.001), unaware of their HIV status (NNTI = 2.2 vs. 4.2, P = 0.009), not on ART (NNTI = 2.1 vs. 4.9; P < 0.001), not enrolled in a methadone program (NNTI = 3.3 vs. 10.4, P < 0.001), reported injecting <5 years (NNTI = 3.3 vs. 5.0; P = 0.005), or from Nairobi (NNTI = 3.2 vs. 5.6, P < 0.001). Conclusion: Scaling up APS among PWID living with HIV with certain characteristics could result in more efficient APS and greater partner engagement in HIV care.